Non-Invasive Dynamic Reperfusion of Microvessels In Vivo Controlled by Optical Tweezers - Shao, Meng; Zhong, Min-Cheng; Wang, Zixin; Ke, Zeyu; Zhong, Zhensheng; Zhou, Jinhua (Frontiers in Bioengineering and Biotechnology, 2022)
Distributive shock is considered to be a condition of microvascular hypoperfusion, which can be fatal in severe cases. However, traditional therapeutic methods to restore the macro blood flow are difficult to accurately control the blood perfusion of microvessels, and the currently developed manipulation techniques are inevitably incompatible with biological systems. In our approach, infrared optical tweezers are used to dynamically control the microvascular reperfusion within subdermal capillaries in the pinna of mice. Furthermore, we estimate the effect of different optical trap positions on reperfusion at branch and investigate the effect of the laser power on reperfusion. The results demonstrate the ability of optical tweezers to control microvascular reperfusion. This strategy allows near-noninvasive reperfusion of the microvascular hypoperfusion in vivo. Hence, our work is expected to provide unprecedented insights into the treatment of distributive shock.